Forest management, policies and politics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Managing Africa's tropical dry forests - a review of indigenous methods by Gill Shepherd 1992 117pp ISBN 0 85003 169 9 Pbk UKL9.95